2019
DOI: 10.1177/2455747119889915
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Children’s Independent Mobility in Dhaka

Abstract: Children’s mobility environment is an ignored topic in discussions of sustainable urbanisation in the Global South. This study explores the independent mobility of children from ages 7 to 15 in Dhaka—reportedly the world’s densest urban conglomeration. Surveys and interviews of children ( n = 308) and their parents were conducted in eight schools in Dhaka, located in three strategically selected residential areas. Children’s independent mobility (CIM) was then analysed with reference to relevant themes across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…In children, this prevalence is consistent with other recent studies conducted in other Spanish cities 19 . Compared to the rest of the world, the prevalence of IM in children was slightly lower than that found in Germany and England 10 and in adolescents the prevalence of IM was slightly higher than that found in Finland and Asia 11,18 . Available evidence suggests a wide range of variables such as age, gender, family background, socioeconomic status and the structure of their neighbourhoods, as important individual, social and environmental factors that influence IM in children and adolescents 20 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In children, this prevalence is consistent with other recent studies conducted in other Spanish cities 19 . Compared to the rest of the world, the prevalence of IM in children was slightly lower than that found in Germany and England 10 and in adolescents the prevalence of IM was slightly higher than that found in Finland and Asia 11,18 . Available evidence suggests a wide range of variables such as age, gender, family background, socioeconomic status and the structure of their neighbourhoods, as important individual, social and environmental factors that influence IM in children and adolescents 20 .…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, there were no significant changes in IM rates among Spanish children and adolescents during the 2010–2017 period. Opposite results were found previously in several studies, which have reported a decline in IM rates among children and adolescents from 1971 to 2010 10,11,18 . The absence of changes in IM rates in Spain showed in the current study could be reflect the policies that Spanish society had adopted into potentiate more active and independent behaviours in the population.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations